Nesting ecology of Mottled Ducks Anas fulvigula in interior Florida, USA - Dugger, Bruce D; Finger, Richard; Malvin, Stefani L (Wildfowl, 2013)
Little is known about the breeding biology of Mottled Ducks Anas fulvigula that occupy the interior portions of Florida, USA. During 1997–1999, radio-transmitters were attached to 82 female Mottled Ducks to locate and characterise nest sites, and to estimate nesting propensity, clutch size, nest success and season-specific adult survival. Mean nest initiation date (n = 25) occurred relatively early in the wet year compared to the dry year. Vegetation height at nests averaged 68.8 ± 6 cm, modal canopy cover was 100% and mean distance of nests from water was 188 ± 41 m. Vegetation characteristics at nests were similar to those reported in other parts of the species range, but dominant plant species differed and nests were located farther from water than previously reported. Modal clutch size was 10 eggs (range = 7–14) and nest success for all years combined was 0.095 (95% C.I. = 0.032–0.268). Survival estimates for adult females during a 15-week interval (26 February to 10 June) were 0.902 ± 0.016 in 1998 and 0.879 ± 0.016 in 1999. Nesting propensity (22–50%) and nest success were the lowest reported for Mottled Ducks.